2018
DOI: 10.1038/s41598-018-30615-2
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin Inhibits Neural Induction of Human Induced Pluripotent Stem Cells

Abstract: Tributyltin (TBT), one of the organotin compounds, is a well-known environmental pollutant. In our recent study, we reported that TBT induces mitochondrial dysfunction, in human-induced pluripotent stem cells (iPSCs) through the degradation of mitofusin1 (Mfn1), which is a mitochondrial fusion factor. However, the effect of TBT toxicity on the developmental process of iPSCs was not clear. The present study examined the effect of TBT on the differentiation of iPSCs into the ectodermal, mesodermal, and endoderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…These results suggest that changes in mitochondrial membrane permeability may be involved in the mechanism for the anesthesia-induced enhancement of mitochondrial fission in the developing brain. In addition to the in vivo studies, Mfn has been reported to mediate neural differentiation from human induced pluripotent stem cells, which are commonly used for DNT evaluation in vitro [72,73]. Several DTXs, including tributyltin and 5-fluorouracil, have been reported to induce degradation of Mfn protein and subsequently inhibit neural differentiation [72,74].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that changes in mitochondrial membrane permeability may be involved in the mechanism for the anesthesia-induced enhancement of mitochondrial fission in the developing brain. In addition to the in vivo studies, Mfn has been reported to mediate neural differentiation from human induced pluripotent stem cells, which are commonly used for DNT evaluation in vitro [72,73]. Several DTXs, including tributyltin and 5-fluorouracil, have been reported to induce degradation of Mfn protein and subsequently inhibit neural differentiation [72,74].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…In addition to the in vivo studies, Mfn has been reported to mediate neural differentiation from human induced pluripotent stem cells, which are commonly used for DNT evaluation in vitro [72,73]. Several DTXs, including tributyltin and 5-fluorouracil, have been reported to induce degradation of Mfn protein and subsequently inhibit neural differentiation [72,74]. Thus, it would be useful to include examination of mitochondrial dynamics in the evaluation of DTXs in vivo and in vitro.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollutants such as nitrogen dioxide and particulate matter, too, have been associated with an increased risk of developing ASD [ 109 111 ]. Employing iPSC models, Yamada et al studied exposure of neural cells to the environmental pollutant tributyltin [ 112 ] and the organophosphate and insecticide chlorpyrifos [ 113 ], both of which have been linked to an increased risk of ASD in offspring [ 114 , 115 ]. Their data suggest that both substances lead to reduction of MFN1 and thus to mitochondrial dysfunction, which subsequently impairs neural induction [ 112 , 113 ].…”
Section: Asd-related Phenotypes In 2d Modelsmentioning
confidence: 99%